Diagnostics of soils located in the gradient of urban-technogenic impact - S. G. Novikov; M. V. Medvedeva; A. N. Pekkoev; V. V. Timofeeva (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The rapidly progressing urbanization results in decline of environmentally valuable forest territory. Intact ecosystems bordering urban communities suffer from heavy technogenic pressure and degrade irreversibly over time. This situation necessitates studies that analyze the ecological condition of major components of forest ecosystems exposed to various levels of such pressure. The survey was carried out in the city of Petrozavodsk in sites with degraded, slightly disturbed, and undisturbed forest ecosystems. For each site, the soil condition was assessed, the tree stand and the living ground cover were described. As a result, it was found that soils in the slightly disturbed forest ecosystem generally corresponded to the natural background (Ferric Illuvial Podzol). Changes in their morphological and chemical properties compared to soils in the undisturbed reference plot were identified. The thickness and ash content of the upper organic horizon in the slightly disturbed site changed. The forest ecosystem was in the transitional stage (from I–II to III) of recreational digression and required infrastructural improvements. The forest ecosystem in the built-up site was totally destroyed. Irreversible transformation of its natural environment resulted in the loss of woody and ground vegetation. The native zonal soils were ruined, and their diagnostic horizons cannot be identified. There was observed a large amount of rocks and anthropogenic inclusions throughout the profile. According to the Russian soil classification, these formations belong to the subgroup of organo-mineral strata of technogenic surface formations. The collected data can be used as the basis for ecological monitoring of urban soils. Based on the findings, recommendations were given on how to conserve and improve the sanitary and esthetic functions of forest areas adjoining urban built-up land.